A qualitative analysis exploring barriers and enablers to distribution, delivery, and access to COVID-19 vaccines in Botswana - Tlhakanelo, John T.; Ataguba, John Ele-Ojo; Pagiwa, Vincent; Ramabu, Nankie; Kadimo, Khutsafalo; Muriithi, Grace Njeri; Achala, Daniel Malik; Adote, Elizabeth Naa Adukwei; Mbachu, Chinyere Ojiugo; Beshah, Senait Alemayehu; Masuka, Nyasha; Nwosu, Chijioke Osinachi; et al. (Frontiers in Health Services, 2025)
IntroductionThe COVID-19 pandemic highlighted pre-existing weaknesses, revealing deep-rooted issues in infrastructure, access, and resource allocation that have long impeded African countries' ability to effectively meet population health needs. It also became evident during the pandemic that there were discrepancies in how vaccines were distributed, delivered and accessed in these countries. We aimed to identify vaccine distribution, service delivery processes and related barriers in Botswana to contextually explore practices that either enhance or hinder access and equity in vaccine distribution and delivery.MethodsWe conducted in-depth interviews, using a semi-structured interview guide, with a purposive sample of 18 key informants, including public health sector officials, non-state actors, policy makers, regulatory bodies and other stakeholders. Interviews were audio-recorded and transcribed verbatim. Thematic analysis was conducted following a deductive approach according to the six-step analysis framework by Braun and Clarke: (i) familiarization with the data; (ii) generation of initial codes; (iii) searching for themes; (iv) reviewing themes; (v) refining and naming themes; and finally, (vi) producing the report. Steps i–iii were conducted by two researchers. Attention was given to aspects of credibility, dependability, and transferability of the findings through key strategies, including team data review, coding, consensus on themes and review of both secondary and grey literature on vaccine roll-out in the country.ResultsSeven primary themes emerged from the findings. COVID-19 vaccine distribution and delivery in Botswana followed the existing primary health care system structures for routine vaccine delivery. Traditional mechanisms such as static public health facilities, private facilities, outreach campaigns, and mobile stops, were augmented through different roles played by stakeholders in the private sector, civil society organizations and non-governmental organizations. Religious and cultural norms were reported to affect vaccine uptake centered around smaller population groups that are historically known to be anti-vaccines. There is no deliberate gender and the disabled population programming for vaccine distribution and delivery in Botswana. The private sector improved access to vaccines by supporting supply chain logistics with transportation, especially to hard-to-reach areas.DiscussionsAchieving equitable vaccine access involves not only logistical and infrastructural considerations, but also coordination and collaboration across several sectors, enhancing gender diversity and inclusivity in planning, coordination, and decision making and implementation of strategies tailored to the needs of a wide range of vulnerable population groups.